2019
DOI: 10.3329/bjp.v14i3.40292
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis, cytotoxic, antioxidant and anti-diabetic activities of the aerial parts of Sorghum halepense

Abstract: Phytochemical screening, cytotoxic activity, total phenolic content, antioxidant and anti-diabetic activities of the Sorghum halepense methanolic extract and its different fractions were evaluated. Methanolic extract and its various fractions revealed the presence of reducing sugars, tannins, steroids,  glycosides, flavonoids in the methanolic extract where they were absent in n-hexane fraction except flavonoids. Gums and saponins were absent in all the samples. Methanolic extract indicated the highest cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Meanwhile, flavonoids prevent oxidative stress development by inhibiting enzymes producing free radicals. 34 The outcome of this research has further verified the increases in plasma TG, TC, VLDL, and LDL, and the decrease in HDL indicated significant dyslipidemia in DC rats.…”
Section: Discussionsupporting
confidence: 57%
“…Meanwhile, flavonoids prevent oxidative stress development by inhibiting enzymes producing free radicals. 34 The outcome of this research has further verified the increases in plasma TG, TC, VLDL, and LDL, and the decrease in HDL indicated significant dyslipidemia in DC rats.…”
Section: Discussionsupporting
confidence: 57%
“…The TPC of the Andropogon halepensis aqueous leaf extract, determined using the Folin–Ciocalteu method, was 20.83 ± 0.96 mg GAE/g dry extract. Shah et al had previously reported a TPC value of 20.3 ± 1.5 mg GAE/g dry extract for the aerial parts of S. halepense aqueous extract [ 36 ], and Mohammed et al [ 37 ] reported a polyphenol content of 20.78 ± 1.83 mg GAE/g dry extract for an aqueous extract of aerial parts of Beta vulgaris.…”
Section: Resultsmentioning
confidence: 99%